Ngā Kupu Arotau - Eweri Tāima: Loanwords in Māori 1842-1952 - Ka'ai, Tania; Moorfield, J. C. (Te Ara Poutama, Auckland University of Technology, 2009)
Māori has adopted a significant number of loanwords that have enriched the language. Following a description of the loanwords project and the database, it will be shown that words borrowed into Māori adapt to not only the phonological system but also the grammatical system of Māori. As expected, a loanword is not likely to have exactly the same connotations as the foreign word from which it has been borrowed. It may have more restricted meanings or have taken on new meanings and connotations not encompassed by the foreign word from which it is derived. A major outcome of the project has been the collection of a large database of loanwords from the Māori-language newspapers, the Paipera Tapu (the Māori Bible) and a few other 19th century sources. This database has been converted to an historical loanwords dictionary now available free online.